Long-term relationship of crude palm oil commodity pricing under structural break - Ayojimi, Salami Monsurat; Haron, Razali (Emerald Publishing Limited, 2018)
The purpose of this paper is to examine the pricing efficiency of the Malaysian crude palm oil (CPO) market before and after the structural break. This study uses the daily closing price of CPO and CPO futures (CPO-F) for the period ranging from June 2009 to August 2016 while taking structural breaks into account. In this study, symmetric and asymmetric long-run relationship model are employed,such as the Johansen cointegration,VECM,TAR and M-TAR models,to examine the impact of structural breaks on the pricing efficiency of the Malaysian CPO market. This finding establish that Malaysian CPO price is efficient before and after the structural break. The consistent efficiency of the Malaysian CPO market supports the trading of the CPO-F in Globex and the use of Malaysian CPO pricing as the reference price. This study establishes that a structural break in the Malaysian CPO price series does not affect the pricing efficiency of the market. This study shows that using Malaysian CPO price as a reference price is sustainable even in the event of a structural break. Therefore, market participants in the Malaysian CPOmarkethavelesstoworryabouttheCPOpriceasitsupportstheweakformofefficiency.Pricedeviation in the short run may not lead to arbitrage profit as transaction cost may not be covered. Practical implications – This study implies that if there is distortion in the price due to shocks, both manufacturers and producers need to hedge their positions in the futures market(subject to their positions in the underlying market). By entering into the futures market, pricing is locked in advance; hence, price risk is eliminated. Such a distortion could also affect the efficiency of the CPO price, therefore this study also addresses the issue of efficiency of the local CPO market. Previous studies on Malaysian CPO pricing efficiency did not take the effect of structural break into consideration, making it difficult for these studies to show consistency in the efficiency of the Malaysian CPO market.